Studi Kasus: Peran Harakat dalam Pembacaan Teks Bahasa Arab Bagi Pemula di Pondok Pesantren Zainul Hasan Genggong - Vivi Febrianti; Ainur Rafiq Sofa (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to explore the role of harakat in assisting beginner students at Pondok Pesantren Zainul Hasan Genggong in reading and understanding Arabic texts. Learning Arabic, especially for beginners, presents its own challenges, particularly in reading texts that use the harakat system. Harakat plays a crucial role in proper pronunciation and understanding the meaning of words. This study uses a qualitative descriptive method with a case study approach, involving 1) seventh-grade students and 2) the arabic language teachers in that class. The results of the study show that harakat significantly helps students in understanding Arabic grammar, improving reading skills, and comprehending the meaning of texts. Additionally, internal factors such as physical health, as well as external factors like family conditions, also influence students' ability to read Arabic texts. Based on the findings of this study, it is recommended that the use of harakat in teaching Arabic to beginners be maintained and enhanced.